Using of Plastic Wastes as Additives in Bituminous Mixes - Abu El-Maaty, Ahmed Ebrahim; Ibrahim Sourour, Ibrahim Reda; El-Sayed Bekheet, Wael Ali (Applied Science and Engineering Progress, 2021)
Plastic wastes are everywhere in today’s lifestyle and are growing rapidly specially in a developing country like Egypt. As these are non-biodegradable, there is a main issue facing the community concerning the handling of this plastic rubbish. On the other hand, different forms of increased distresses in flexible pavements such as cracking and rutting as well as moisture damage ratio should be faced and reduced by modifying the performance of hot asphalt mixtures. The reclaimed plastics that originally made of polymers have been used as an anti-stripping modifier to reduce the appearance of distresses in asphalt pavement surface and increase the resistance against moisture damage. In this research, the recycled plastic wastes have been used according to dry mixing process using contents (0.0, 2.0, 3.0, 4.0 and 5%) from the total weight of hot asphalt mixture. The optimal bitumen content has been derived for each polymer content by using Marshall procedure. The performance of modified bitumen mixtures have been recognized using Marshall quotient (as indicator of the stiffness), static indirect tensile strength and tensile strength ratio (as indicator of moisture damage resistance), dynamic modulus value (as indicator of stiffness of the asphalt mixture when tested in a compressive and repeated load test under different temperatures) and flow number (as indicator of permanent axial deformation resistance). The results obtained that the addendum of plastic rubbish to HMA improves its characteristics such as stability, strength, resistance to moisture damage and permanent deformation. The addition ratio of 3% polymer provides better pavement performance. Moreover, it has an economic importance where it reduces the exhaustion of natural asphalt in paving works by about 14.5%.